Carbon Emission Disclosure And Green Accounting Practices On The Firm Value - Wenni Anggita; Ari Agung Nugroho; Suhaidar (Jurnal Akuntansi, 2022)
This research was conducted to analyze and examine how the effect of disclosure of carbon emissions and green accounting practices to firm value with a sample of customer goods companies in Indonesia. The measurement of carbon emission disclosure will use the check list obtained from the Carbon Disclosure Project proposed by Choi et al., 2013 while the Green Accounting Practice uses the Global reporting index contained in the company's financial statements. This study wants to measure how actually Carbon emission disclosures and Green accounting practices affect the firm value. By using the legitimacy theory that focuses on the company's relationship with the community and its environment, then of course the company will always make improvements and prevention of environmental problems that will have an impact on the existence of the company. The company will certainly do various ways, one of which is by conducting carbon emission disclosures which are expected to gain legitimacy so that the company has a level of sustainability. The sample of this study is 16 customer goods companies in Indonesia with an observation period of 2 years 2019-2020 so that there are 32 observation data. By using multiple linear regression of panel data, the results of the study suggest that carbon emission disclosure have no influence or no effect on firm value meanwhile green accounting practices affect on firm value.